Determining the Effects of Participatory Teaching Methods on Students’ Learning of Mathematics and Biology in Tanzania - Michael, Muhangwa Godfrey (Progress in Language, Literature and Education Research Vol. 8, 2024)
This paper originates from a study on the effects of interactive teaching methods on students' learning of mathematics and biology at Tanzania's ordinary level secondary schools in Mwanza region. The qualitative technique was used in conjunction with the quantitative data. The 111 participants were chosen using simple random selection and selective sampling methods. Purposeful sampling was used to identify participants who could provide in-depth insights related to the participatory methods versus learning outcomes. Characteristics such as expertise, experiences and specific attributes were employed. To enhance generalizability of quantitative findings, random sampling technique was used to ensure that each member of the population has an equal chance of being selected. In addition, the study collected data via surveys, interviews, focus groups, observations, and documentary reviews. In contrast to the content analysis that was performed on the qualitative data, the quantitative data were analysed through processes like data cleaning, coding variables, dispersion and frequency distribution henceforth, bar charts, histogram, tables, figures and percentages were developed to facilitate interpretation. The research revealed that students had a positive attitude toward participative teaching methods and a desire to learn. According to studies, students' comprehension of math and biology at a basic level can be improved by adopting participatory teaching methods supported by suitable T/L materials and qualified teachers.